Revision of the genus Thyreocephalus and description of Afrus gen. nov. of Africa south of the Sahara (Coleoptera: Staphylinidae: Staphylininae) - Janák, Jiří; Bordoni, Arnaldo (Zootaxa, 2015)
A revision of the genus Thyreocephalus Guérin-Méneville, 1844 of Africa south of the Sahara is presented. A new genus Afrus gen. nov. was described with the type species Thyreocephalus spegazzinii Bernhauer, 1915, which resulted in following new combination: Afrus spegazzinii (Bernhauer, 1915), comb. nov. Eulissus collarti (Cameron, 1932) was transferred to Afrus. Based on a revision of types and of additional material, 32 species of the genus Thyreocephalus and two species of the genus Afrus are recognized in Africa south of the Sahara. All species are described or redescribed and illustrated, seven of them for the first time: Thyreocephalus camerunensis sp. nov., T. manfredi sp. nov., T. marginipennis sp. nov., T. meridioafricanus sp. nov., T. pseudoafricanus sp. nov., T. subcorticalis sp. nov. and T. tsingidianus sp. nov. Neotypes are designated for Eulissus ater Laporte, 1835, Xantholinus coeruleipennis Quedenfeldt, 1881, and X. interocularis Eppelsheim, 1895. Lectotypes are designated for Eulissus atlanticus Bernhauer, 1915, E. burgeoni Bernhauer, 1929, E. mokaensis Bernhauer, 1915, E. secretus Bernhauer, 1935, E. turneri Bernhauer, 1937, Xantholinus alluaudi Fauvel, 1907, X. mocquerysi Fauvel, 1903, X. pilosus Roth, 1851, Thyreocephalus diversiceps Bernhauer, 1936, and T. spegazzinii Bernhauer, 1915. Eulissus africanus Bernhauer, 1913, E. alluaudi (Fauvel, 1907) (originally described in Xantholinus Dejean, 1821), E. atlanticus Bernhauer, 1915, E. brunneiventris Tottenham, 1956, E. burgeoni Bernhauer, 1929, E. guineensis Bernhauer, 1912, E. mokaensis Bernhauer, 1915, E. secretus Bernhauer, 1935, E. strinatii Scheerpeltz, 1958, and Xantholinus nairobiensis Fauvel, 1907 were transferred to Thyreocephalus. Following synonymies are proposed: Thyreocephalus nairobiensis (Fauvel, 1907) = Eulissus turneri Bernhauer, 1937, syn. nov., Thyreocephalus interocularis (Eppelsheim, 1895) = Thyreocephalus diversiceps Bernhauer, 1936, syn. nov., Thyreocephalus mokaensis (Bernhauer, 1915) = Eulissus flaviventris Bernhauer, 1939, syn. nov. = Thyreocephalus semirufus Coiffait, 1968, syn. nov., Thyreocephalus mocquerysi (Fauvel, 1903) = Eulissus milliaui Bernhauer, 1932, syn. nov. The distribution of both genera in Africa south of Sahara is mapped and a key to species is presented.